Seismic vulnerability assessment of a 17th century adobe church in the Peruvian Andes - Briceño Melendez, Carolina (2018)
A large part of Peruvian heritage corresponds to Colonial Andean churches, which are economically and culturally essential for the development of several villages. Particularly, adobe churches are very vulnerable to earthquakes due to the brittle material behavior, the weak connections, and the absence of a rigid diaphragm. This article aims at performing the seismic vulnerability assessment of an adobe heritage church: “Virgen de la Asuncion” of Sacsamarca located in the province of Ayacucho in the Andean region of Peru; using a rapid screening method and a more complex numerical analysis. First, the damage survey was carried out through visual inspection and infrared thermography, while the material characterization was performed by applying flat-jack tests. Later, the seismic vulnerability assessment was carried out in two stages. The first was based on simplified criteria for masonry structures, and the other on a pushover analysis of global performance. From this evaluation, it was possible to conclude that the church is indeed vulnerable to Peruvian seismic demands.